The doctrine of God in reformed Orthodoxy, Karl Barth, and the Utrecht School : a study in method and content. - Velde, Dolf te. (Studies in Reformed Theology, 2013)
In The Doctrine of God Dolf te Velde examines the interaction of method and content in three historically important accounts of the doctrine of God. Does the method of a systematic theology affect the belief content expressed by it? Can substantial insights be detected that have a regulative function for the method of a doctrine of God? This two-way connection of method and content is investigated in three phases of Reformed theology. The first seeks to discover inner dynamics of Reformed scholastic theology. The second part treats Karl Barth's doctrine of God as a contrast model for scholasticism, understood in the framework of Barth's theological method. The third part offers a first published comprehensive description and analysis of the so-called Utrecht School. The closing chapter draws some lines for developing a Reformed doctrine of God in the 21st century.